Corea del Sur y el coronavirus de las cosas - López Aymes, Juan Felipe (El Colegio de México A.C., 2021)
2019 concluded with an outstanding approval to Moon Jae-in’s administration, after an agitated and intense year full of events that will continue to reverberate for the upcoming years. Institutional reforms to the electoral system, the prosecution office, the police, and the spy agency kept their turbulent track on the legislative arena, but only managed to get the approval of a National Assembly party representation reform, yet not without pushing and shoving. Inter-Korean diplomacy had important setbacks and will complicate Moon’s goal to establish a new peace regime in the Korean peninsula; relations with Japan remained strained as controversies about bilateral history invaded the economic and cultural areas, which mostly had had their own untainted course for the last two decades. Finally, it is clear to everybody that no nation escaped from the great upheaval caused by the Covid-19 pandemic in 2020, although some had fared better than others, and South Korea seems to be one of those cases.